Transcultural Aspects of Warriorship - Milčinski, Maja (Journal of Dharma, 2007)
Circa 1200 B.C. marks two famous events in the history of humankind of a very similar character. They were certainly not directly connected, since they occurred in two widely distant lands. One took place in the north-western part of Asia Minor, the other far away on the wide plains of Kuru Kshetra, close to Hastinapur, today’s New Delhi.